Development of Teaching Materials in Writing Text Report of Project Based Observations (Problem Based Learning) for Class X SMK Telkom 2 Medan - Eva Damayanti Damanik; Khairil Ansari; Malan Lubis (BIRCU, 2020)
This study aims to determine the results of the development of teaching materials to write project-based observation report text for class X SMK Telkom 2 Medan. The subjects of this study were students of class X SMK Telkom 2 Medan who were taken as many as 1 class / study group with a total of 30 students. Researchers collected information based on the results of observations of teaching materials in class X SMK Telkom 2 Medan shows that the teaching materials used by teachers so far have only used textbooks without teaching materials in the form of modules as another guide in learning, especially on the text material for the observation report. The results of the effectiveness of teaching materials for writing text c reports on the results of project-based observations (project based learning) on a limited trial, namely 30 students of class X SMK Telkom 2 Medan, namely in the pretest test results obtained an average score of 68.97% with sufficient category . Meanwhile, after using teaching materials to write text modules on the postest test with an average score of 80.83% with a good category. These results state that the teaching materials for writing project-based observation report text after use have a significant increase in student learning outcomes with a difference of 11.86 which indicates that by using the teaching materials to write project-based observation report text learning) student scores are better than before.